Multilocular cystic hemangioma of the liver mimicking mucinous cystic neoplasm: a case report - Nam Kyung Lee (Journal of Yeungnam Medical Science, 2022)
Hepatic hemangiomas infrequently exhibit atypical imaging features, which may cause diagnostic confusion with hepatic malignancies and lead to unnecessary surgery. We report a rare case of multilocular cystic hemangioma of the liver mimicking a mucinous cystic neoplasm of the liver in a 48-year-old female, focusing on computed tomography and magnetic resonance imaging features and their differential diagnosis.